ANALYSIS OF FACTORS AFFECTING THE PERFOMANCE OF SMALL TRADERS IN SURAKARTA - Endah Nawangsasi (STIE AUB Surakarta, 2019)
The aim of the research is to know : 1) The influence of product to marketing productivity, 2) The influence of price to marketing productivity, 3) The influence of place to marketing productivity, 4) The influence of promotion to marketing productivity, 5) The stimulant influence of product, price, place and promotion to marketing productivity. The location of search in Jongke Traditional Market, Surakarta in year 2005/2006. The population of research is all of small seller in Jongke Market. The sample takes by the proportional random sampling with count of respondent is 50 small seller. Data can found by the questionare with the validity dan reliability test. The data analyze, using statistic data analyze with multiple regression technique and do it with SPSS program. The result of research conclude that : 1) There are the significant influence between product with marketing productivity, 2) There are the significant influence between price with marketing productivity, 3) There are the significant between place with marketing productivity, 4) There are the significant influence between promotion with marketing productivity, 5) There are the significant simultant influence between product, price, place, and promotion with marketing productivity. Keywords: marketing mix, marketing performance, small traders, tradition market